Ramularia collo-cygni--An Emerging Pathogen of Barley Crops - Havis, Neil D; Brown, James K M; Clemente, Gladys; Frei, Peter; Jedryczka, Malgorzata; Kaczmarek, Joanna; Kaczmarek, Maciej; Matusinsky, Pavel; McGrann, Graham R D; Pereyra, Sylvia; Piotrowska, Marta; Sghyer, Hind; et al. (Phytopathology, 2015)
Ramularia collo-cygni is the biotic factor responsible for the disease Ramularia leaf spot (RLS) of barley (Hordeum vulgare). Despite having been described over 100 years ago and being considered a minor disease in some countries, the fungus is attracting interest in the scientific community as a result of the increasing number of recorded economically damaging disease epidemics. New reports of disease spread and fungal identification using molecular diagnostics have helped redefine RLS as a global disease. This review describes recent developments in our understanding of the biology and epidemiology of the fungus, outlines advances made in the field of the genetics of both the fungus and host, and summarizes the control strategies currently available.
Keywords: Hordeum; Host-Pathogen Interactions; interakce hostitele a patogenu; Plant Diseases; nemoci rostlin; Pest Control; Ascomycota; ječmen (rod); kontrola škůdců